Living language : an introduction to linguistic anthropology - Ahearn, Laura M., 1962- (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2012)
"Accessible and clearly written, Living Language: An Introduction to Linguistic Anthropology introduces readers to the study of language in real-life social contexts around the world through the contemporary theory and practice of linguistic anthropology. A highly accessible introduction to the study of language in real-life social contexts around the world Combines classic studies on language and cutting-edge contemporary scholarship and assumes no prior knowledge in linguistics or anthropology Provides a unifying synthesis of current research and considers future directions for the field Covers key topics such as: language and gender, race, and ethnicity; language acquisition and socialization in children and adults; language death and revitalization; performance; language and thought; literacy practices; and multilingualism and globalization"--
"Living Language: An Introduction to Linguistic Anthropology is a clear and accessible exploration of the prominent theoretical issues in linguistic anthropology and a student-friendly introduction to the study of language in real-life social contexts around the world. Combining classic studies on language in social contexts and cutting-edge, contemporary scholarship, Ahearn provides a unifying synthesis of research in linguistic anthropology and looks towards future research in the field. Treating language as inextricably intertwined with culture and social relations Living Language combines theory with examples of contemporary language use to explore the way in which language creates, maintains, challenges, and reconfigures social hierarchies. Chapter topics include gender, race, and ethnicity, language acquisition and socialization, performance, literacy practices, multilingualism, and globalization. Laura Ahearn introduces the fascinating field of linguistic anthropology as well as underlining the value of an ethnographically grounded approach to the study of language"--
Includes bibliographical references and index.
Keywords: Anthropological linguistics; Language and culture; SOCIAL SCIENCE / Anthropology / Cultural